2015
DOI: 10.1002/jcp.24940
|View full text |Cite
|
Sign up to set email alerts
|

Shear Stress Modulates Resistin‐Induced CC Chemokine Ligand 19 Expression in Human Aortic Endothelial Cells

Abstract: Resistin may be an important link between obesity and diabetes. Recent studies have suggested an association between resistin and atherogenic processes. In addition, CCL19 is highly expressed in human atherosclerotic lesions. The interplays among resistin, CCL19, and shear stress in regulating vascular endothelial function are not clearly understood. In the present study, resistin stimulation induced dose- and time-dependent CCL19 expression in human aortic endothelial cells (HAECs). By using neutralizing anti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 36 publications
0
6
0
Order By: Relevance
“…TLR-4 is recognized to have a key function in the host defence against Gram-negative bacteria, viruses, fungi and mycoplasma [10], but also in the patho-physiology of several age-related diseases [9,11], including CVDs, as stressed in our studies [4,8,11,12] and described by other groups [13][14][15]. Recently, its role has emerged in maintaining aortic homeostasis, but also in establishing aorta aneurysm [4,8,[16][17][18][19][20][21][22][23][24][25][26][27][28][29].…”
Section: Introductionmentioning
confidence: 77%
See 1 more Smart Citation
“…TLR-4 is recognized to have a key function in the host defence against Gram-negative bacteria, viruses, fungi and mycoplasma [10], but also in the patho-physiology of several age-related diseases [9,11], including CVDs, as stressed in our studies [4,8,11,12] and described by other groups [13][14][15]. Recently, its role has emerged in maintaining aortic homeostasis, but also in establishing aorta aneurysm [4,8,[16][17][18][19][20][21][22][23][24][25][26][27][28][29].…”
Section: Introductionmentioning
confidence: 77%
“…In fact, the role of TLR-4 mediated receptor signaling pathway in the context of aorta diseases is also emerging [16][17][18][19][20][21][22][23][24][25][26][27][28][29]. In particular, our group postulates its fundamental contribution to the development of sporadic TAA, as reported in the above mentioned model [4,8].…”
Section: Toll-like Receptor-4 (Tlr-4) Signaling Pathway In Aorta Homementioning
confidence: 92%
“…p38-MAPK pathway is critical for resistin-induced SDF-1 expression mediated by TLR4 in gastric cancer cells 23 . Additionally, HR Yu et al demonstrated that TLR4 is critical for resistin-induced CCL19 expression using a neutralizing antibody and siRNA in human aortic endothelial cells 24 . Our data showed that pharmacological inhibitors of TLR4 and TLR4 siRNA application could inhibit resistin-induced CCL4 expression, which was further confirmed with co-immunoprecipitation.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the decreased expression of CCL19 in the B cell zones of mature TLSs was probably due to the decreased percentages of other CCL19‐secreting cells, such as fibroblasts 22 and endothelial cells. 23 T cells in the B cell zones of immature TLSs were with higher expression of naïve T cell marker SELL (Table S9 ) and an increased T naïve signature (Figure 4C ; Table S10 ). Antigens are presented by FDCs to B cells and by B cells and DCs to T cells in the B cell zones of TLSs.…”
Section: Resultsmentioning
confidence: 99%